Efficacy of Transversus Abdominis Plane Block in the Reduction of Pain and Opioid Requirement in Laparoscopic and Robot-assisted Hysterectomy: A Systematic Review and Meta-analysis - Claudia López-Ruiz; Jerutsa Catalina Orjuela; Diego Fernando Rojas-Gualdrón; Marcela Jimenez-Arango; José Fernando de los Ríos; Elsa Maria Vásquez-Trespalacios; Claudia Vargas (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To summarize the available evidence of TAP Block in efficacy in laparoscopic or robotic hysterectomy. Data Sources We searched databases and gray literature for randomized controlled trials in which transversus abdominis plane (TAP) block was compared with placebo or with no treatment in patients who underwent laparoscopic or robot-assisted hysterectomy. Method of Study Selection Two researchers independently evaluated the eligibility of the selected articles. Tabulation, Integration, and Results Seven studies were selected, involving 518 patients. Early postoperative pain showed a difference in the mean mean difference (MD): - 1.17 (95% confidence interval [CI]: - 1.87-0.46) in pain scale scores (I2=68%), which was statistically significant in favor of using TAP block, but without clinical relevance; late postoperative pain: DM 0.001 (95%CI: - 0.43-0.44; I2=69%); opioid requirement: DM 0.36 (95%CI: - 0.94-1.68; I2=80%); and incidence of nausea and vomiting with a difference of 95%CI=- 0.11 (- 0.215-0.006) in favor of TAP. Conclusion With moderate strength of evidence, due to the high heterogeneity and imbalance in baseline characteristics among studies, the results indicate that TAP block should not be considered as a clinically relevant analgesic technique to improve postoperative pain in laparoscopic or robotic hysterectomy, despite statistical significance in early postoperative pain scale scores. Clinical Trial Number and Registry: PROSPERO ID - CRD42018103573.